Entrepreneurship and Innovation in the Fight Against Human Trafficking - Bain, Christina (Social Inclusion, 2017)
There has been much discussed and written on the benefits of entrepreneurship education, as well as the importance of early access to this type of learning. But how can entrepreneurship education train and inspire the next generation of anti-trafficking leaders? How can entrepreneurship also be a driver for prevention and a source of economic stability for those at-risk and survivors of human trafficking? At present, there are entrepreneurs and entrepreneurs-in-training at multiple age levels coming from a variety of backgrounds, incomes, and circumstances who will develop groundbreaking strategies and solutions in the fight against trafficking. These current and future entrepreneurs can also provide fresh perspectives to those in government and business while building more effective tri-sector coalitions and partnerships that address human trafficking. This article explores how and why entrepreneurship can be a key vehicle for social change and innovations in combating human trafficking, along with providing a multi-ingredient recipe of prosperity for those most vulnerable.